2009
DOI: 10.1016/j.vaccine.2009.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Human PIV-2 recombinant Sendai virus (rSeV) elicits durable immunity and combines with two additional rSeVs to protect against hPIV-1, hPIV-2, hPIV-3, and RSV

Abstract: The human parainfluenza viruses (hPIVs) and respiratory syncytial viruses (RSV) are the leading causes of hospitalizations due to respiratory viral disease in infants and young children, but no vaccines are yet available. Here we describe the use of recombinant Sendai viruses (rSeVs) as candidate vaccine vectors for these respiratory viruses in a cotton rat model. Two new SeV-based hPIV-2 vaccine constructs were generated by inserting the fusion (F) gene or the hemagglutinin-neuraminidase (HN) gene from hPIV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 87 publications
0
50
0
Order By: Relevance
“…In addition to providing a mouse model to study respiratory paramyxovirus dissemination and pathogenesis, Sendai virus is also a promising Jennerian vaccine candidate against HPIV1 (1,56) and vaccine vector for preclinical HPIV2, HPIV3, and HRSV vaccines (57)(58)(59)(60)(61)(62)(63). There are no confirmed cases of pathogenic Sendai virus infection in humans, and i.n.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing a mouse model to study respiratory paramyxovirus dissemination and pathogenesis, Sendai virus is also a promising Jennerian vaccine candidate against HPIV1 (1,56) and vaccine vector for preclinical HPIV2, HPIV3, and HRSV vaccines (57)(58)(59)(60)(61)(62)(63). There are no confirmed cases of pathogenic Sendai virus infection in humans, and i.n.…”
Section: Discussionmentioning
confidence: 99%
“…Unmodified wild-type SeV elicits protective immunity against HPIV1 without causing adverse events in nonhuman primates (17,40) and is associated with no adverse events after intranasal inoculation into seropositive humans (18). Just as SeV is a promising Jennerian vaccine candidate against HPIV1, rSeV too is being developed as a vaccine vector against HPIV3, as reported here and in our earlier study (15), and other respiratory paramyxoviruses such as HRSV (13,14,41) and HPIV2 (16). Intranasal vaccination with the SeV-vectored HRSV vaccine, in which the HRSV F gene was inserted into the F-HN gene junction of rSeV, elicits protective immunity without causing pathology in both cotton rats (14) and African green monkeys (42).…”
Section: Discussionmentioning
confidence: 52%
“…Recombinant SeV remains an attractive candidate as a respiratory vaccine vector because of its high production capacity in chicken eggs, its restricted host range, its immunogenicity and protective capacity in animal models, and its apparent safety to date in seropositive adults and children. Previous studies have shown that a single, mixed vaccine cocktail of rSeV(F-HN) vaccines can protect cotton rats against challenge from multiple human pathogens, including HPIV1, HPIV2, HPIV3, and RSV (15,16). Our finding that that the attenuated rSeV-HPIV3HN(P-M) vaccine was highly immunogenic and protective in cotton rats raises the possibility of engineering a single rSeV with multiple inserted foreign genes to target multiple pathogens such as HPIV1, HPIV3, and RSV from the same vector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-reactivity applies to virus-specific B-and T-cells, and targets several distinct viral proteins. 13,14 SeV is pathogenic in mice, but is not known to cause disease in humans; SeV is now being developed as a xenotropic vaccine administered intranasally to prevent hPIV-1 infection or disease, and also as a delivery system (vector) for antigens from other human viruses including hPIV-3, 15 hPIV-2, 16 and RSV [17][18][19][20] and more recently for HIV. [21][22][23][24] SeV is also used as a vector to deliver human fibroblast growth factor 2, 25 and angiopoietin-1, 26 genes for the treatment of peripheral artery disease, oncolytic virotherapy, 27 and cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%